2016
DOI: 10.2174/1874149501610010061
|View full text |Cite
|
Sign up to set email alerts
|

Overall Stability Analysis of Improved Buckling Restrained Braces

Abstract: Abstract:In order to improve the behavior of double-tube buckling restrained braces (BRBs), it is proposed to set contact rings between inner tube and outer tube of the brace. As a result, they can provide lateral constraint for the inner tube; this is the improved buckling restrained braces (IBRBs). In this paper, a program was edited by the language of MATLAB based on theoretical model formulation of IBRBs and applied to the calculation of overall stability strength capacity. Finite element models of IBRBs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Since then, Yin et al [27] added a contact ring between the inner and outer components to improve the doubletube BRB. Finite component analysis and tests showed that this support has good energy dissipation performance, and the lateral stiffness of the inner tube confined with the contact rings is significantly improved [28,29]. Hence, this BRB could be introduced to SCBF systems to replace the traditional support to address the limitation of premature buckling.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, Yin et al [27] added a contact ring between the inner and outer components to improve the doubletube BRB. Finite component analysis and tests showed that this support has good energy dissipation performance, and the lateral stiffness of the inner tube confined with the contact rings is significantly improved [28,29]. Hence, this BRB could be introduced to SCBF systems to replace the traditional support to address the limitation of premature buckling.…”
Section: Introductionmentioning
confidence: 99%
“…In past researches, there were many on the end plate connection type energy dissipation beam, but few on the web connection type. Based on the previous researches [42][43][44][45], it can be found that the failure of the end plate connection type energy dissipation link is mainly due to the failure of the flange and the failure of the weld, which reduces the constraint of the flange on the web and further leads to the reduction of the bearing capacity of the link. This paper presents an experimental research program that utilizes web connections at the link-to-beam interface.…”
Section: Introductionmentioning
confidence: 99%
“…|vqwR=t w "|OOa pOt QO |O=yvW}B Ov@ Q=yt |xOvyOp}mWD <= RH= V}=tv "8 pmW Q= Ri=sQv "CU=10 T=tD w 9 Kr=Yt ' 8 |UOvy |]NQ}e pt=a xU Qy pt=W '|OOa xDW=O ?U=vt CkO =@ = Q xOW Qm P pt=wa s=tD |R=Ux}@W C}r@=k O}=@ xOW xO=iDU= CLD w[a QO |rm w |a[wt Vv=tm Q}_v |}=yxO}OB `wkw p}rO x@ u}vJty "OW=@ QorL 'O=}R , =D@Uv K]U =D |Q}tN |=yVvQm `wkw u}vJty w |}xNQJ |Q=PoQ=@ |=y|UQQ@ T=U= Q@ "OW=@ xDW=O pL |xt=O= w |Q=O}=B QO |}q=@ C}r@=k O}=@ Q= Ri=sQv R=}v OQwt |=yC}r@=k12 Twm=@; w 11 T}Uv= |xDiQW}B Q= Ri=sQv wO 'xOt; pta x@ 'Q[=L VywSB QO , =D}=yv "OvQ=O = Q |O=yvW}B Ov@ Q=yt Q=DiQ |r}YiD |R=UpOt |= Q@ "CU= xOW s=Hv= Twm=@; OwOLt <= RH= Q= Ri=sQv R= xO=iDU= =@ |OOa |=y|R=UpOt |xrwr wO R= pmWDt 'Q[=L |xar=]t QO |O=yvW}B Ov@ Q=yt '|m}R}i Q_v R= w Q]k x@ C@Uv u}}=B Ct=N[ x@ xHwD =@ xrwr wO Qy |= Q@ xm 'CU= xOw@ wDQOwD x@ xHwD =@ =t= "OUQ|t Q_vx@ ?U=vt |}xDUwB |=yu=tr= R= xO=iDU= 'xvwtv pw] xOw@ xO}J}B |]NQ}e Q=DiQ pt=W |R=UpOt OQwt |xrUt '|Q=DiQ Q_v R= xmu}= |xDUw}B |=yu=tr= =Pr &CU= ptDLt u; QO |a[wt Vv=tm `wkw XwYN x@ w |rm Vv=tm Q}_v |}=yxO}OB xm |Dr=L QO "Ow@ Ovy=wN |QD?U=vt ?=NDv= |tHL xDUw}B |=yu=tr= 'Ovvm x@ QHD |}q=@ |Q}tN VvQm '=yu=tr= w OvyO MQ |a[wt =} |=ypmWQ}}eD w VvD `} RwD u}vJty "CW=O Ovy=wN w[a Q=DiQ R= |QDy@ V}=tv xO=O V}=tv QDy@ '|}xDUwB |=yu=tr= =@ xU}=kt QO xDUw}B |=yu=tr= QO xO=ONQ "OW Oy=wN 20 w |]N 'pw= |x@DQt |}xQo 8 CQwYwO x@ Twm=@; QO xDUw}B |=yu=tr= QO 'Q= Ri=sQv |=tvy= Q T=U= Q@ "OvDUy xO=iDU= p@=k |]NQ}e 'swO |x@DQt |}xQo |x@DQt |]N |=yu=tr= R= xO=iDU= CQwY QO 'Vv=tm Q}_v |}=yxO}OB |R=UpOt "OwW pQDvm O}=@ w CU= ptDLt 13 |WQ@ |oOWpik |xO}OB `wkw C3D8 pw= Vy=m = Q |WQ@ |oOWpik `wkw p=tDL= 'xDi=}Vy=m |Q}op= QoDv= VwQ R= xO=iDU= =@ |O=yvW}B w[a Q=DiQ |UQQ@ Qw_vt x@ Q[=L |xar=]t QO 'u}= OwHw =@ "OyO|t |x@DQt |=yu=tr= "CU= xOW xO=iDU= |}xQo 20 |]NQ}e |=yu=tr= R= 'QDW}@ CkO "OvyO|t V}=tv QDy@ = Q |a[wt pmWQ}}eD |=ypLt QO , =YwYN VvD `} RwD 'swO R= |QDy@ V}=tv 'pw= |x@DQt |=yu=tr= x@ C@Uv swO |x@DQt |=yu=tr= xwqa x@ "Ovvm|t x=Q= =ypmWQ}}eD `wkw u=tr= 'Q[=L VywSB QO xOW xO=iDU= u=tr= 'xOW x=Q= C=L}[wD T=U= Q@ V}=tv "OwW|t xO=iDU= xDi=}Vy=m |Q}op= QoDv= Cr=L QO xm 'CU= |}xQo 20 OQ=wt s=tD QO 'T=U= u}= Q@ "CU= C3D20R CQwY x@ Twm=@; QO QwmPt u=tr= |Ov@Vt '8 pmW QO "CU= xOW xO=iDU= Ct=N[ QO u=tr= wO smCUO R= '9 pmW QO w |OOa pOt hrDNt <= RH= w |OOa |R=Ux}@W QO xOWxO=iDU= "OwW|t xOy=Wt xOW xO=iDU= |Ov@Vt "|Q=PoQ=@ |=yxNQJ s=tD= R= Oa@ |rN=O |xDUy pmWQ}}eD "12 pmW "|Q=PoQ=@ |=yxNQJ s=tD= R= Oa@ |HQ=N hqe pmWQ}}eD "13 pmW xm OyO|t u=Wv pmDwQB |=yDv= QO |HQ=N hqe w |rN=O |xDUy pmWQ}}eD |RH w |r=tDL= |=yCWv p}rO x@ 'V}=tR; R= pY=L Q=Owtv QO |RH |=yVQB 13 w 12 pmW QO ? }DQD x@ |Q=PoQ=@ "CU= |Q=PoQ=@ sDU}U |xawtHt QO uewQ "OwW|t xOy=Wt u=Wv `w[wt u}= w CU= OwyWt 12 pmW QO |rN=O |xDUy Vv=tm Owt hqe w pN=O |xDUy u}@ T=tD |R=UpOt QO |OOa pOt ?U=vt OQmrta R= O=H}= VvD |xv}W}@ 'pmW Qy QO xOW x=Q= VvD QwDv=m T=U= Q@ "OQ=O |HQ=N u=Wv `w[wt u}= xm 'CU= xOw@ p=mU=B=ot 148 OwOL '|HQ=N hqe QO xOW |HQ=N hqe w xOw@ u=UWm |xOwOLt QO , qt=m |HQ=N hqe Q=DiQ OyO|t QO xOW O=H}= VvD |xv}W}@ "CU= xDW=Ov |QwLt |Q@Q=@ QO |DmQ=Wt xvwo I}y '|rN=O |xDUy OyO|t u=Wv xm 'CU= xOw@ p=mU=B=ot 458 Q@=Q@ |rN=O |xDUy sR}v=mt xm OR=U|t u=Wv Q]=N "CU= xO}UQ s}rUD |xrLQt x@ , qt=m Q=_Dv= j@] |WWm |=yxNQJ QO xDUy |r=wDt s}rUD 'Ov@Q=yt `wv u}= QO |SQv= hqD= |rY= "CU= |Q=Wi w |Q}oxH}Dv "6…”
mentioning
confidence: 99%